2018
DOI: 10.1002/bab.1657
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine induces apoptosis and autophagy via the AMPK/mTOR signaling pathway in pancreatic cancer cells

Abstract: Gemcitabine (GEM)-based chemotherapy is a commonly used treatment for pancreatic cancer. However, acquired drug resistance, a major problem in pancreatic cancer treatment, causes a reduction in the survival rate of patients with cancer. In this study, we attempted to reveal the molecular mechanism of GEM resistance. Our data showed that GEM treatment inhibits cell growth, induces apoptosis, and activates autophagy via the AMP-activated protein kinase (AMPK) pathway. The combination of GEM treatment and AMPK kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…IHC staining also showed that Gem induced CC3 and CC8 expression in vivo. These observations are consistent with those presented in our previous report [ 8 ] and those of others [ 7 , 15 ]. Gem induces apoptosis more potently than other basic agents, such as methotrexate, doxorubicin, cisplatin, and ifosfamide, and may therefore be a key drug for treating OS through the induction of apoptosis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…IHC staining also showed that Gem induced CC3 and CC8 expression in vivo. These observations are consistent with those presented in our previous report [ 8 ] and those of others [ 7 , 15 ]. Gem induces apoptosis more potently than other basic agents, such as methotrexate, doxorubicin, cisplatin, and ifosfamide, and may therefore be a key drug for treating OS through the induction of apoptosis.…”
Section: Discussionsupporting
confidence: 94%
“…Since then, several clinical trials using Gem have been conducted and recently, additional clinical studies on Gem in combination with docetaxel have been evaluated in various adult sarcomas, including OS [ 9 , 10 , 11 , 12 ]. We also reported that Gem strongly induces apoptosis in OS cells in vitro and in vivo [ 8 ]; however, several other reports have shown that Gem induces autophagic cell death [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 98%
“…The mTOR pathway is considered as one of regulating mechanisms responsible for cell sensitivity to GEM. Such relation was already proved in various cancers including breast and pancreatic 33 , 34 , 35 . Yang et al investigated the mechanism of resistance to GEM in breast cancer model, they noted hyperactivation of mTOR pathway in cells insensitive to treatment with GEM.…”
Section: Discussionmentioning
confidence: 71%
“…The most important is using only 2D models of uterine sarcomas and carcinosarcoma, such models are easily reproducible and allow to perform isobolographic analysis of relations between tested substances, but on the other hand do not fully reflect behaviour of tumours in vivo . Secondly, the reported project do not include any mechanistic research, partially the activity mechanisms of used compounds were previously described 4 , 5 , 5 , 7 , 26 , 29 , 30 , 33 , 35 but further studies aimed to describe mechanisms of cellular response to combined treatment are strongly indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Zyflamend treatment induced ER stress, autophagy, MAP kinases and apoptosis in pancreatic β-TC6 Cells. Previous studies have shown that activation of AMPK in pancreatic cancer cells by chemotherapeutic agens induces apoptosis and autophagy via the AMPK/mTOR signaling pathway (dotted lines) [ 47 ]. Similarly, activation of the JNK/SAPK pathway [ 48 ] by stressors and chemotherapeutic agents can lead to apoptotic cell death of pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%